« tutto quest’ordine con più ornamento » : la pensée ornementale de Michel-Ange - Lizzie Boubli (Images Re-Vues)
Ornament’s question seems easy to imply when we think about Michelangelo’s personality. There are therefore few studies concerning his relation with ornament, often studied with changes operated in various projects. This article proposes a first inspection on ornament’s position by indirectly means their more significant realizations. By this way, we perceive that ornament answers as well as the whole to harmony and sense’s requirements. It shapes an inseparable meaning, completes or enlightens a work’s signification (Tondo Doni, for instance). At the end of his life, ornament is more and more reduced. The human figure is now perceived in transcendent relationship with the sacred field and fill place of balance between ornament and figure. But without ornament’s implication, would Michelangelo aimed to represent human form with such intensity?